Asymptomatic COVID‐19: disease tolerance with efficient anti‐viral immunity against SARS‐CoV‐2. Issue 6 (27th May 2021) - Chan, Yi‐Hao; Fong, Siew‐Wai; Poh, Chek‐Meng; Carissimo, Guillaume; Yeo, Nicholas Kim‐Wah; Amrun, Siti Naqiah; Goh, Yun Shan; Lim, Jackwee; Xu, Weili; Chee, Rhonda Sin‐Ling; Torres‐Ruesta, Anthony; Lee, Cheryl Yi‐Pin; et al.
Abstract: The immune responses and mechanisms limiting symptom progression in asymptomatic cases of SARS‐CoV‐2 infection remain unclear. We comprehensively characterized transcriptomic profiles, cytokine responses, neutralization capacity of antibodies, and cellular immune phenotypes of asymptomatic patients with acute SARS‐CoV‐2 infection to identify potential protective mechanisms. Compared to symptomatic patients, asymptomatic patients had higher counts of mature neutrophils and lower proportion of CD169 + expressing monocytes in the peripheral blood. Systemic levels of pro‐inflammatory cytokines were also lower in asymptomatic patients, accompanied by milder pro‐inflammatory gene signatures. Mechanistically, a more robust systemic Th2 cell signature with a higher level of virus‐specific Th17 cells and a weaker yet sufficient neutralizing antibody profile against SARS‐CoV‐2 was observed in asymptomatic patients. In addition, asymptomatic COVID‐19 patients had higher systemic levels of growth factors that are associated with cellular repair. Together, the data suggest that asymptomatic patients mount less pro‐inflammatory and more protective immune responses against SARS‐CoV‐2 indicative of disease tolerance. Insights from this study highlight key immune pathways that could serve as therapeutic targets to prevent disease progression in COVID‐19. Synopsis: Whole blood transcriptomic analyses highlight distinct immune responses during acute phase of disease. Asymptomatic patients elicit a more robust TH17 response compared to symptomatic patients. Asymptomatic patients present a less inflammatory profile, with lower counts of CD169 + monocytes, activated neutrophils, and a muted inflammatory response. Higher levels of cellular repair biomarkers are also observed in asymptomatic patients. Abstract : We show that asymptomatic patients elicit a different repertoire of immune responses from symptomatic patients. Our data suggest that asymptomatic patients could limit symptom development with a well‐balanced inflammatory response and more protective immune responses against SARS‐CoV‐2.